Resistensi Perempuan terhadap Konstruksi Gender dalam Film La Source des Femmes karya Radu Mihăileanu - Rizki Amalia Pertiwi (Faculty of Languages and Arts, Universitas Negeri Padang, 2021)
Issues regarding gender issues are closely related to women and how their roles are constructed in social life, which creates various stereotypes that lead to gender inequality problems. In the film La Source des Femmes, gender construction is shown through narrative and cinematographic aspects. This article focuses on women's resistance to gender construction that have taken shape in the lives of remote rural women in Morocco. The analysis in this article uses a film study by Boggs and Petrie (2012) and Actor Scheme by Greimas (1967). James C. Scott's concept of resistance and Mansour Fakih's gender inequality were also used to deepen the analysis. This research is a qualitative research with descriptive method. The data in the study are in the form of words, clauses, phrases, or sentences that indicate the form of women's resistance. The findings of the analysis show that the resistance shown by rural Moroccan women aims to fight the injustice of their roles and obligations as women and housewives who have been oppressed and have directly harmed them. Through this research, it is also seen that the resistance carried out by village women has an impact on their growing awareness of self-subjectivity and redefining their role as a woman.